Die: Between Conventional And Digital Techniques An in vitro comparative study - Baherli, Nasser; chammout, Muhammad Marwan (Latakia University Journal -Medical Sciences Series, 2020)
There are currently many materials that can be used in the manufacture of Models and Dies which are satisfactory in terms of possessing the desired features with some bad properties for each. In order to overcome these bad properties and get accurate work Models and Dies without distortions, we must have a precise impression material and use materials to make Models and Dies are stable,so many digital impression and 3D printing techniques have been developed to manufacture the Dies based on them. It has not been studied and compared with existing materials. This study was conducted to compare many materials and conventional and digital methods in the manufacture of the Dies to reach the best and most accurate way in the context of the manufacture of fixed prosthodontics that is accurate, fit and durable. The first lower right molar[Frazaco] was prepared to receive a full ceramic crown. Two impression techniques were used, one using conventional plastic and metal trays ,condensation silicone impression and the other using digital scanner by Smart Optics. We used five different methods in the manufacture of Models and Dies, including four traditional depending on the gypsum stone Model IV and also on epoxy resin with or without air vacuum. The fifth method used is based on digital techniques. After the completion of the Models and Dies, the process of measuring the three dimensions [length, width and height] of the Dies began based on the Exocad dental program used in CAD [ computer assisted design]. Within the limits of this in – vitro study, the following conclusions were drawn: There are no significant statistical differences regarding Dies made from digital impression with 3D printing when compared with the main Die in terms of the three dimensions studied. While the Dies made of gypsum stone Model IV from conventional impression using a plastic trays without air vacuum showed significant statistical differences. Dies made of gypsum stone Model IV from conventional impression using a metal trays with or without air vacuum have shown expansion slightly. The epoxy resin Dies from conventional impression using a metal tray with vavuum showed minimal contraction. تتوافر حالياً العديد من المواد يمكن استخدامها في تصنيع الأمثلة و النماذج الإفرادية, والتي تعتبر مرضية من حيث امتلاكها للميزات المرغوبة, مع وجود بعض الخواص السيئة لكل منها. و لتجاوز هذه الخواص السيئة والحصول على أمثلة عمل و نماذج إفرادية دقيقة بدون تشوهات, يجب أن نمتلك مادة طابعة دقيقة ونستخدم مواد لصناعة الأمثلة و النماذج الإفرادية تكون مستقرة, لذلك تم تطوير العديد من تقنيات الطبعات الرقمية و الطباعة ثلاثية الأبعاد لتصنيع النموذج الإفرادي اعتماداً عليها, و لكن لم تتم دراستها و مقارنتها مع المواد الموجودة حالياً. أجريت هذه الدراسة لمقارنة العديد من المواد و الطرق التقليدية و الرقمية في تصنيع النموذج الإفرادي, للوصول إلى الطريقة الأفضل و الأكثر دقة في سياق تصنيع تعويضات ثابتة تتمتع بالدقة و الانطباق و الديمومة. تم تحضير رحى أولى سفلية يمنى [ سن فرازاكو ] و ذلك لاستقبال تاج خزفي كامل. تم استخدام تقنيتين لأخذ الطبعة واحدة تقليدية باستخدام الطوابع البلاستيكية و المعدنية و المطاط السيليكوني التكثيفي, و أخرى رقمية باستخدام الماسح الخاص بشركة Smart Optics. قمنا باستخدام خمس طرائق مختلفة في تصنيع الأمثلة و النماذج الإفرادية, أربع منها تقليدية اعتماداً على الجبس الحجري من النموذج الرابع و كذلك على راتنج الإيبوكسي مع أو بدون تخلية هوائية, أما الطريقة الخامسة المستخدمة فهي تعتمد على التقنيات الرقمية [ طبعة + طباعة ثلاثية الأبعاد ]. بعد الانتهاء من تصنيع مثال العمل, بدأت عملية القياس للأبعاد الثلاثة [ الطول و العرض و الارتفاع ] للنموذج الإفرادي, اعتماداً على برنامج Exocad dental المستخدم في عمليات التصميم بمساعدة الكمبيوتر CAD. ضمن حدود هذه الدراسة في المختبر تم استخلاص النتائج التالية: عدم وجود فوارق إحصائية هامة بما يخص النماذج المصنوعة انطلاقاً من الطبعة الرقمية مع الطباعة ثلاثية الأبعاد عند المقارنة مع النموذج الإفرادي الرئيسي؛ من حيث الأبعاد الثلاثة المدروسة. بينما أظهرت النماذج المصنوعة من الجبس الحجري انطلاقاً من طبعة تقليدية باستخدام طابع بلاستيكي بدون تخلية هوائية فوارق إحصائية هامة. أبدت النماذج المصنوعة من الجبس الحجري النموذج الرابع انطلاقاً من طبعة تقليدية باستخدام طابع معدني مع أو بدون تخلية هوائية تمدداً ضئيلاً. بينما أظهرت النماذج المصنوعة من راتنج الإيبوكسي انطلاقاً من طبعة تقليدية باستخدام طابع معدني مع تخلية هوائية تقلصاً ضئيلاً.